Estudo quanti-qualitativo da autopercepção de ageismo por pessoas idosas durante a pandemia da covid-19 no Amazonas - Santoro, Márcia Batista (2023)
Brazil was one of the countries most impacted by the COVID-19 pandemic, especially the State of Amazonas, which reached its peak between May 2020 and February 2022. Advanced age was soon recognized as one of the main risk factors for development of clinical complications and death, related to pre-existing comorbidities. In this context, age-related prejudice, which has existed for a long time, became more evident during the pandemic. The formation of negative and ageist stereotypes can be the basis of the prejudiced construction in relation to old age that culminates in discrimination and even violence. That said, studies have been and continue to be carried out around the world based on the self-perception of this population segment about ageism during the pandemic period. In this sense, it is important that these studies are also carried out with the Brazilian population, in particular the Amazonian population, with whom the research took place. The main objective was to evaluate the self-perception of elderly people in relation to ageism during the COVID-19 pandemic in the State of Amazonas. The research was conducted through a quantitative-qualitative study related to the self-perception of elderly people regarding situations of ageism during the COVID-19 pandemic. The quantitative observational and cross-sectional epidemiological study involved the application of the Ageism Scale in the COVID-19 Pandemic (EA-COVID-19) modified from the Ageism Survey instrument (Palmore, 2000). to experiences of ageism during the COVID-19 pandemic. Both studies were conducted in a population composed of elderly people aged 60 years or over, which included socially active men and women, regular participants in the activities of the Fundação Universidade Aberta da Terceira Idade (FUNATI) of Amazonas. The results showed that the majority of interviewees (61.4%) agreed that they had suffered one or three situations of ageism. The two most frequent self-perception questions about ageism were that the Pandemic worsened discrimination and prejudice against older people, followed by the selfperception of having felt discriminated against by health professionals due to their age. In the qualitative analysis, mesostructural and macrostructural ageism was seen, mostly of explicit origin. Concluding that 75% of those interviewed suffered two or more situations of ageism, it characterizes the reason why ageism has gained the attention of bodies and institutions linked to the elderly, researchers and society in general.